Evaluasi Kualitas Website SMA Negeri 1 Balikpapan Menggunakan Metode Webqual 4.0 dan Importance-Performance Analysis (IPA) - Dini Rahmatika Adi; Satrio Hadi Wijoyo; Niken Hendrakusma Wardani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2020)
SMA Negeri 1 Balikpapan is one of the public schools in the city of Balikpapan that utilizes the website as a media to facilitate the school in matters relating to information management and support the productivity in the dissemination of information around the school. The website is rated to have poor quality based on its user experience in terms of display quality to the information that was delivered. Therefore, it is necessary to assess the website's quality using Webqual 4.0 and the IPA method to improve and maintain the quality website. Webqual 4.0 assesses the scope of the problem that includes usability, information quality, and service interaction while the IPA method is used to look at the problems that are a priority improvement. Data collection was carried out by distributing questionnaires to 302 students who used the website of SMA Negeri 1 Balikpapan. The results of the study showed that there are 5 attributes included in top priorities, ease of operation, clarity of interaction, and navigation on the website as well as the display and layout of information. While the 4 attributes that are included in the low priority are the suitability of the website display type, timeliness of information, the suitability of information submitted, and the ease of communication of students and teachers through the website. The rest attribute does not have a priority fix because it has enough performance to maintain. Repair recommendations are given to attributes that go in the top and low priorities and it refer to HHS Usability Guidelines and ISO 9241-151.